Relationship between Knowledge and Attitude about Prevention of Diabetes Mellitus Complications in Diabetes Mellitus Patients - Henrianto Karolus Siregar; Khairunnisa Batubara; Hanna Ester Empraninta; Fatima Ura Pabanne (University of Muhammadiyah Semarang, 2021)
Diabetes mellitus is a chronic disorder characterized by hyperglycemia characterized by defects in insulin secretion, insulin action or both. Attitudes of patients regarding complications of diabetes mellitus need to be approached to patients who have diabetes mellitus. The number of people with Diabetes Mellitus in the world from year to year has increased, this is related to the increasing population, increasing life expectancy, urbanization which changes traditional lifestyles to modern lifestyles, obesity increases and physical activity decreases. Knowledge of patients with diabetes mellitus can be interpreted as the result of knowing from patients about their disease, understanding the disease, and understanding prevention, treatment and complications. This study aims to identify the relationship between knowledge and attitudes of patients with diabetes mellitus about complications of diabetes mellitus. This study is descriptive with 105 samples and data collection techniques using Convinience Sampling. Collecting data using a questionnaire that has been validated and reliability using the Cronbach alpha test. The results showed that the knowledge of diabetes mellitus patients about complications of diabetes mellitus was categorized as good as many as 83 respondents (79.0%). It can be used as a guideline for carrying out nursing care for patients with diabetes mellitus in order to realize the desired nursing goals and evaluations such as health workers are expected to further increase their role in providing health education about the prevention of complications of diabetes mellitus.